Hidradenitis Suppurativa as a Potential Subtype of Autoinflammatory Keratinization Disease - Nomura, Toshifumi (Frontiers in Immunology, 2020)
Hidradenitis suppurativa (HS) is a chronic inflammatory skin condition, clinically characterized by boiled cysts, comedones, abscess, hypertrophic scars, and/or sinus tracts typically in the apocrine gland-rich areas such as axillae, groins, and/or buttocks. Although its precise pathogenic mechanisms are not fully elucidated, I herein emphasize the importance of the following 3 recent discoveries in the pathogenesis of HS. First, heterozygous loss-of-function mutations in the genes encoding γ-secretase, including NCSTN, PSENEN, and PSEN1, have been identified in some patients with HS. Such genetic alterations result in hyperkeratosis, dysregulated hair follicle differentiation, and cyst formation via aberrant Notch signaling. Furthermore, Psen1-/Psen2-, Psen1-, Ncstn+/-, and Notch1-/Notch2- mice share common phenotypes of human HS, suggesting the role of aberrant keratinization in the development of HS. Second, upregulation of IL-1β, IL-36, caspase-1, and NLRP3 and dysregulation of the Th17:Treg cell axis have been demonstrated in HS samples, suggesting that autoinflammation is a key event in the pathophysiology of the disease. Notably, HS may be complicated with other autoinflammatory diseases such as inflammatory bowel diseases and pyoderma gangrenosum, again highlighting the importance of autoinflammation in HS. Lastly, biologics such as adalimumab, infliximab, anakinra, ustekinumab, and secukinumab have been reported to be effective for moderate-to-severe HS. These findings collectively suggest that HS is closely linked with aberrant keratinization and autoinflammation, raising a question whether it represents an autoinflammatory keratinization disease (AIKD), a recently proposed disease entity. In this mini review, I will introduce the concept of AIKD and attempt to address this clinically important question.